Jawa-Islam-Cina : politik identitas dalam Jawa safar Cina sajadah - Tomoidjojo, Cin Hapsari (Jakarta : Wedatama Widya Sastra, 2012)
Political identity of Javanese and Chinese in Jawa safar Cina sajadah, a Javanese proverb.
Includes bibliographical references (p. 303-314).
Keywords: Chinese -- Indonesia -- Java; Islam -- Indonesia -- Java